DIE EPILOOG VAN DIE OPENBARING AAN JOHANNES (22:6-21) - Müller, Bethel A. (Scriptura, 1982)
The epilogue to St John’s revelation The epilogue (22:6-21) offers a key to the interpretation of Revelation as a whole. An exegetical analysis of this periscope reveals a reciprocal relationship between a heavenly and an earthly liturgy, which on every level is supported by an eschatological motivation. This relationship consists of a liturgical denouement (7-10), gathering (12-14), prayer (16-19) and concentration (20). This analysis is followed by some hermeneutical remarks (section II) and finally by some homiletical implications (section III).